Prototype of Smart Grain Storage Based Internet of Things - Pratama, Wahyu Adi; Nurchim, Nurchim; Pamekas, Bondan Wahyu (Jurnal Inotera, 2024)
Rice (Oryza sativa L.) is a crucial staple food, particularly in Indonesia, one of the largest rice-producing countries. Proper storage of rice grains is essential to maintain their quality and quantity. This research aims to develop a smart rice grain storage prototype based on the Internet of Things (IoT) that can monitor temperature, humidity, and light intensity in real-time. The method used is Design-Based Research (DBR), involving six stages: focus, understanding, definition, conception, creation, and testing. The prototype utilizes DHT22 sensors for temperature and humidity, LDR sensors for light intensity, and soil moisture sensors, all integrated with an ESP32 microcontroller. Data collected from the sensors are sent to a cloud-based platform for analysis and early warnings if storage conditions are unsuitable. The results indicate that the prototype effectively monitors storage conditions and provides accurate data. System testing shows that all components function according to specifications. This prototype helps maintain grain quality and reduce damage risk during storage. The use of IoT in grain storage enhances efficiency and reduces farmers' costs. Future research should focus on developing more advanced prototypes with automatic control features and mobile application integration.